Light‐induced agglomeration of single‐atom platinum in photocatalysis - Denisov, Nikita; Qin, Shanshan; Will, Johannes; Vasiljevic, Bojana Nedić; Skorodumova, Natalia V.; Pašti, Igor A.; Sarma, Bidyut Bikash; Osuagwu, Benedict; Yokosawa, Tadahiro; Voß, Johannes; Wirth, Janis; Spiecker, Erdmann; et al. (Advanced Materials, 2022)
With recent advances in the field of single-atoms (SAs) used in photocatalysis, an unprecedented performance of atomically dispersed co-catalysts has been achieved. However, the stability and agglomeration of SA co-catalysts on the semiconductor surface may represent a critical issue in potential applications. Here we describe the photoinduced destabilization of Pt SAs on the benchmark photocatalyst, TiO2. In aqueous solutions within illumination timescales ranging from few minutes to several hours, light-induced agglomeration of Pt SAs to ensembles (dimers, multimers) and finally nanoparticles takes place. The kinetics critically depends on the presence of sacrificial hole scavengers and the used light intensity. DFT calculations attribute the light induced destabilization of the SA Pt species to binding of surface-coordinated Pt with solution-hydrogen (adsorbed H atoms), which consequently weakens the Pt SA bonding to the TiO2 surface. Despite the gradual aggregation of Pt SAs into surface clusters and their overall reduction to metallic state, which involves >90% of Pt SAs, the overall photocatalytic H2 evolution remains virtually unaffected.<br